ANALISIS SEGMENTASI PASAR BERDASARKAN DEMOGRAFIS DAN PERILAKU DIDASARKAN MANFAAT PADA NASABAH KREDIT PT. BPR MITRA RAKYAT RIAU KOTA PEKANBARU - restuti, Sri (Jurnal Tepak Manajemen Bisnis, 2015)
This study aims to analyze the characteristics of the market segmentation of the Customer Credit PT. BPR Mitra Rakyat Riau based on demographics and behavior based on the merits, to analyze the prioritized segments as a target market and to analyze the competitive strategies are most appropriate. The study population was a credit to all customers in December 2013 amounted to 897 customers. The research sample using Taro Yamane formula amounted to 136 customers.Research results (1) Market segmentation based on behavioral formed consisting benefit from quality service and economical consisting of 8 new factors based on the amount of the interest owned by the accuracy and speed of transactions and complaints officer, the officers ability to serve and lighter penalty charge, suitability capability, flexibility and cost of a light installment, the credibility of the BPR and ease of information, billing procedures and office location, suitability and comfort schedule service, speed of loan disbursements and repayments late fee. With the number of customers as many as 71 people, or 52.20%, (2) segment is prioritized as a target market is the segment 2 with a lot of customers by 71 people, or 52.20%, ie factor 1 (Accuracy and speed of transactions and complaints officer), factor 2 (capability officers in serving and lighter penalty charge), factor 3 (Suitability capability, flexibility and cost lightweight installment), factor 4 (BPR credibility and ease of information), factor 7 (Speed Credit Realization) and factor 8 (penalty delay Instalment). Profile formed on segment 2 are customers aged <25 years, 36-45 years and> 55 years, the last education <high school, high school, S1 / S2, civil servants, entrepreneurs, businessmen / traders, others, and the average income per month for 2 million - 5 million 5 million - 10 million and (3) the competitive strategy is the most appropriate notice the most dominant factor in the credit interest on the first factor on the accuracy and speed of transactions and complaints officer in the indi- indicators: accuracy in obtaining the information, the administrative process in accordance with a predetermined schedule, promptness in servicing the teller cash transactions, alertness of officers serving the complaint, the speed in providing credit information and administrative processes and rapid preparation of credit applicationsKeywords: Market Segmentation, Demographics and Behavior.